Using athletes as role models? Conceptual and empirical perspectives from a sample of elite women soccer players - Guest, A. M.; Cox, S. (International Journal of Sports Science and Coaching, 2009)
Although popular discourse claims that elite female athletes serve as effective role models for a broad set of characteristics, theoretical and empirical perspectives on athletes as role models are sparse and somewhat inconsistent. In exploratory research designed to clarify conceptualizations of athletes as role models by asking for the athlete's own perspectives, we surveyed 39 elite women soccer players in the USA. Drawing primarily on open-ended responses, we found that the players did articulate a consistent cultural script for the characteristics of a role model and felt comfortable with their role-model status. Interestingly, however, that script was not as focused on the athletic prowess that made the players public figures. Instead, the players focused on role models as characterized by meritocratic personality traits (such as being disciplined and hard working) and interpersonal abilities (such as being caring and generous). We discuss implications for those interested in promoting, working with, and studying athletes as role models.